2013
DOI: 10.1021/ie3034569
|View full text |Cite
|
Sign up to set email alerts
|

Phenol Removal Process Development from Synthetic Wastewater Solutions Using a Polymer Inclusion Membrane

Abstract: This paper presents the results concerning the first use of a polymer inclusion membrane (PIM) for the removal and transport of phenol from an aqueous solution and polluted water. The PIM contains Cyanex 923 as the carrier, cellulose triacetate (CTA) as the base polymer, and o-nitrophenyl pentyl ether (ONPPE) as a plasticizer. The effects of variables on the transport percentage of phenol have been studied. These variables include the concentration of the carrier and the plasticizer in the membrane, pH of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…As observed in Figure 5 , M1 shows significantly low extraction of MG as compared to other membranes (with carrier). A similar result was also reported by Pérez-Silva et al [ 49 ] who studied the removal of phenol with PIM. They confirmed that a membrane without a carrier will only be able to transport a low percentage of phenol.…”
Section: Resultssupporting
confidence: 89%
“…As observed in Figure 5 , M1 shows significantly low extraction of MG as compared to other membranes (with carrier). A similar result was also reported by Pérez-Silva et al [ 49 ] who studied the removal of phenol with PIM. They confirmed that a membrane without a carrier will only be able to transport a low percentage of phenol.…”
Section: Resultssupporting
confidence: 89%
“…When the feed solution pH is equal to 2, the removal efficiency of phenol reaches the maximum 95%; this result is in agreement with those obtained by Pérez-Silva et al (2013) and Benosmane et al (2016). The phenol-calix[4]resorcinarene complex was formed by hydrogen bond, in addition the degree of ionization of phenol was comparatively stronger at the higher pH (pH 3) which decreases the complexation rate between calix[4]resorcinarene and phenol.…”
Section: Effect Of Ph Solution Of Feed Phase On the Removal Efficiencsupporting
confidence: 92%
“…In PIMs techniques, a complexant agent, the carrier is immobilized in a base polymer with a plasticizer. In recently conducted studies, we have verified the suitability of PIMs with Cyanex 923 as carrier and CTA as a base polymer to extract phenol from its dilute acidic solution and transport it quantitatively into receiving a solution containing at least 0.25 M of NaOH (Pérez-Silva et al 2013). The PIMs applied in these studies are relatively stable and provide the potential for a safe method for the removal of phenol from dilute aqueous solutions.…”
Section: Introductionmentioning
confidence: 65%
“…Benosmane et al [ 11 ] and Pérez-Silva et al [ 19 ] stated that the pH on the source phase affected the phenol transport, thus the variation on the pH was conducted at the initial stage in this work. The pH variations in the source phase were done at 3.5, 4.5, 5.5, 6.5, and 8 for transporting phenol.…”
Section: Results and Discusionmentioning
confidence: 99%